Refleksi Kristologi Dalam Berbagai Konteks - Mery Cyntia; Cindi Anisa Bahar (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2025)
This article aims to explore the diversity of Christological reflections that emerge in various contexts, namely cultural, social, and interfaith dialog. Christology, the central study in Christian theology regarding Jesus Christ, has undergone significant evolution and adaptation along with its interaction with various historical, social, and cultural backgrounds. This research uses a literature study approach, by collecting and analyzing data from various journals and relevant academic sources to identify and understand how the concept of Christology is reflected and interpreted in different contexts. The results of the analysis show that the reflection of Christology in the cultural context involves the incarnation of positive values of local culture while maintaining a critical perspective on elements that are contrary to Christian teachings. In the social context, Christology becomes a theological foundation to fight for justice and inclusiveness. Meanwhile, in interfaith dialog, Christology acts as a bridge to build understanding and cooperation with adherents of other religions through recognition of uniqueness and potential common ground. This article concludes that a contextual and diverse understanding of Christology not only enriches the treasures of Christian theology, but also strengthens the relevance of Christian faith in the face of the complexity and plurality of the modern world. Thus, continuous and contextualized Christological reflection is essential for Christians to live their faith deeply and make a significant contribution to the global community.